A Usina de Itaipu e a Operação Condor: o outro lado das relações bilaterais Brasil-Paraguai (1973-1987) - Silva, Jussaramar da (2010)
This dissertation objective to discuss the role assumed for the Special Assessorship of Security and Informations of Itaipu Hydroeletric (AESI s), enter the years 1973 up to 1988. These Assessorships had consisted as an arm of the repression in Brazil and Paraguay, as well as of the Condor Operation. During the analyzed period, they had had the role to spy on and to emit reports on the workers of Itaipu, as well as of any people who were considered suspicion in the region of the Tríplice Border. For the understanding of the object in analysis, we launch hand of the expedient to understand the construction of the hydroelectric as form to objectify the model of development of the Brazilian and Paraguayan State, which discharged in the States of National Security, transforming all into internal enemy potentials